Experimental testing of acoustic alarms (pingers) to reduce bycatch of harbour porpoise, Phocoena phocoena, in the state of Washington - J. Gearin, Patrick; E. Gosho, Merrill; L. Laake, Jeffrey; Cooke, Lawrence; DeLong, Robert; M. Hughes, Kirt (J. Cetacean Res. Manage., 2023)
Field tests were conducted on the effectiveness of acoustic alarms (pingers) in reducing the incidental catch of harbour porpoise (Phocoena phocoena) in a salmon gillnet fishery in northern Washington in July and August of 1995-1997. The alarms produced a broadband signal with peaks at 3 and 20kHz, with mean source levels between 121.7-124.7dB re 1mPa @ 1m. For 1995 and 1996 combined, 47 harbour porpoise were taken in control nets and only two were taken in alarmed nets. The alarms significantly reduced the bycatch of harbour porpoise for both seasons (1995: c2 = 5.28, df = 1, p = 0.02; 1996: c2 = 11.2, df = 1, p = 0.001). In 1997, all nets were alarmed and 12 porpoise were taken; however, the expected catch without alarms would have been 79. There were no significant differences in catch rates of chinook salmon (Oncorhynchus tshawytscha) (c2 = 0.31. df = 1, p = 0.58), or sturgeon (Acipenser sp.) (c2 = 1.44, df = 1, p = 0.23) in control or alarmed nets. There were also no significant differences in the bycatch of harbour seals (Phoca vitulina) (c2 = 0.09, df = 1, p = 0.76) or depredation of salmon by seals in nets with and without alarms (c2 = 0.07, df = 1, p = 0.79). The results of these studies indicate that acoustic alarms significantly reduce the probability of harbour porpoise entanglement in bottom-set gillnets in the fishery without reducing the catch of target fish species.